Challenges of Digitalization In The Economy: The Penetration of Sharia Fintech in Aceh - Rosalina, Dhian; Nurhayati, Nurhayati; Anggraini, Tuti (Economics, Business and Management Science Journal, 2025)
Most coastal communities engage in fishing and simultaneously operate as MSMEs (Micro, Small, and Medium Enterprises) that drive the coastal economy. Unequal access to financial services from banks and other financial institutions has created obstacles for MSMEs in accessing financial services. Financial technology (fintech) has become a viable economic solution supporting MSME development by providing quick, affordable, and accessible services.In Aceh Province, where Sharia law is implemented in economic activities, one of the government policies through Bank Indonesia in 2023—"maintaining economic stability with inclusive and green economic-financial policies through digitalization and expanding domestic and export market access for MSMEs and Islamic economic-financial systems"—is particularly relevant to the challenges faced by coastal MSMEs in eastern Aceh. The urgency of this research lies in the need to study the strengthening of Sharia fintech-based financial services to assist MSMEs in the fisheries sector in developing their businesses amidst limited banking services in coastal areas of eastern Aceh.  This research aims to develop a Sharia fintech penetration model that can accelerate MSME growth in the coastal areas of eastern Aceh. This study employs two approaches: the interactive model and SWOT analysis. Research informants will include representatives from Bank Aceh, Bank Syariah Indonesia, the Department of Communication and Information in eastern Aceh, and Sharia fintech providers in Aceh.